Salivary noncoding RNA in the diagnosis of pancreatic cancer: Systematic review and meta‐analysis - Koopaie, Maryam; Kolahdooz, Sajad; Fatahzadeh, Mahnaz; Aleedawi, Zainab Abdulkareem (European journal of clinical investigation, 2022)
Background Pancreatic cancer is considered one of the most deadly malignancies, primarily because of its diagnostic challenges. We performed a systematic review and diagnostic meta‐analysis to evaluate the diagnostic value of noncoding salivary RNAs in pancreatic cancer diagnosis. Methods Our investigation involved pertinent studies published in PubMed, Scopus, Web of Science, LIVIVO, Ovid and also the Google Scholar search engine. Specificity and sensitivity were calculated, as were positive and negative likelihood ratios (PLR and NLR), and the diagnostic odds ratio (DOR). The summary receiver‐operating characteristics and area under the curve were plotted and assessed. Results This meta‐analysis and systematic review involved and examined five studies that contained 145 study units with a total of 2731 subjects (1465 pancreatic cancer patients versus 1266 noncancer controls). The pooled specificity, sensitivity, NLR, PLR and DOR were 0.783 (95% CI: 0.759–0.805), 0.829 (95% CI: 0.809–0.848), 0.309 (95% CI: 0.279–0.343), 3.386 (95% CI: 2.956–3.879) and 18.403 (95% CI: 14.753–22.954), respectively, with the area under the curve (AUC) equal to 0.882. Subgroup analyses were conducted based on the saliva type (unstimulated and stimulated), mean age of patients, sample size, type of control, serum carbohydrate antigen 19–9 (CA19‐9) level and type of salivary noncoding RNA (microRNA (miRNA) and long noncoding RNA (lncRNA)). Conclusions The results of our systematic review and meta‐analysis suggest that noncoding RNA biomarkers in the stimulated saliva could be a promising approach for accurate pancreatic cancer diagnosis in the early stages.